Aorta transplantation in young apolipoprotein E-deficient mice: Possible model for studies on regression of atherosclerotic lesions - Tonar, Zbyněk; Bobková, Dagmar; Witter, Kirsti; Matějka, Vít Martin; Havlíčková, Jana; Lánská, Věra; Poledne, Rudolf (Central European journal of medicine, 2010)
Syngeneic transplantation of murine aorta segments with advanced atherosclerotic lesions in defined recipients is a valuable model for regression studies. To date, this model has not been used to study the regression of initial atherosclerotic lesions. The aim of this study was to evaluate a microsurgical technique of syngeneic heterotopic transplantation of the thoracic aorta of young apolipoprotein E-deficient (ApoE-/-) mice to the abdominal aorta of wild-type recipients. Stereological quantification methods were tested in order to assess changes in structure and volume of the aortic wall including the involvement of immune cells in changes of the atherosclerotic lesions. The animals were euthanised one month after surgery and histological analysis including stereological quantification of changes in both the grafts and adjacent aorta segments was performed. The overall survival rate of the recipients was 62.5%. No regression of initial atherosclerotic lesion was achieved and neointima formation and elastin degradation prevailed in all transplanted specimens. The volume of the arteriosclerotic lesions was higher (p<0.001) and elastin length density was lower (p<0.001) in transplanted ApoE-/- samples as compared to adjacent segments. In transplanted grafts, T- and B-lymphocytes, macrophages and neutrophilic granulocytes formed non-random clusters within the vessel wall and they were colocalised with the sutures. The reproducibility of the promising regression model was derogated in young mice by the striking dependence of the results upon the operation technique. Stereological assessment has proven to be accurate, correct and reproducible; it has provided us with robust quantitative estimates, which can be achieved with a reasonable effort.